2014
DOI: 10.1007/s00520-014-2474-y
|View full text |Cite
|
Sign up to set email alerts
|

The perceived cancer-related financial hardship among patients and their families: a systematic review

Abstract: Evidently, cancer is a long-term illness that requires a high financial cost, and a significant number of cancer patients and families struggle with financial difficulty. Identifying such groups with a high risk of facing financial difficulty is a crucial measure to ensure safety nets are readily available for these targeted population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
124
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 26 publications
5
124
1
2
Order By: Relevance
“…Our results are consistent with prior reports showing that cancer survivors face productivity losses and heavy financial burdens as a result of their disease and related treatment [3, 4, 6, 813, 18, 19]. Previous estimates of the proportion of cancer survivors with financial distress have ranged from 14–78 % [12]. The proportion of cancer survivors filing for bankruptcy—just one of several measures of financial distress we examined—has been previously been estimated at 2.2 % and is similar to findings in our study [10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with prior reports showing that cancer survivors face productivity losses and heavy financial burdens as a result of their disease and related treatment [3, 4, 6, 813, 18, 19]. Previous estimates of the proportion of cancer survivors with financial distress have ranged from 14–78 % [12]. The proportion of cancer survivors filing for bankruptcy—just one of several measures of financial distress we examined—has been previously been estimated at 2.2 % and is similar to findings in our study [10].…”
Section: Discussionsupporting
confidence: 92%
“…In a nationally representative sample, recently diagnosed and previously diagnosed cancer survivors had annual excess economic burdens of over $16,000 and $4000, respectively per survivor, over and above the annual burden of individuals without cancer [11]. Importantly, those experiencing financial distress are more likely to delay or forgo needed medical care—including needed cancer treatments [6, 12]—and are more likely to experience adverse health outcomes, such as anxiety, depression, and poor health-related quality of life [6, 1316]. Accordingly, national policy recommendations include monitoring and support for financial distress in the growing population of cancer survivors [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out-of-pocket expenses reported by our patients were higher than those reported for adult patients with other solid tumours 11,19 . However, lost time from work among our study patients was similar to time lost by breast cancer patients 29,30 .…”
Section: Discussionsupporting
confidence: 66%
“…Given that supplement costs are relatively specific to hnc, it is not surprising that costs in that category are much higher than are seen in other common solid cancers (breast, colorectal, lung, and prostate) 11,19 . We note that our study patients reported more lost time from work than is seen in patients with other cancers 29,30 . Perhaps our capture of multiple time points allowed us to more accurately assess lost-time peaks, which our earlier studies missed with the inclusion of only one time point per person.…”
Section: Figure 2 Duration Of Percutaneous Endoscopic Gastrostomy (Peg)contrasting
confidence: 44%